Tribological behaviour of ductile and austempered grey cast iron under dry environment. (2021) - Akinribide, O.J.; Akinwamide, S.O.; Obadele, B.A.; Ogundare, O.D.; Ayeleru, O.O.; Olubambi, P.A.
Abstract: In the search of appropriate materials for producing machine tools, this study investigated the wear performance of Austempered grey cast iron (AGCI) and ductile iron (DI) done on a single way tribosystem. An alloy containing 1.2 kg of Fe-Si-Mg inoculated by 0.2%Ca-Si was introduced to the melt at 350 °C austempering temperatures after austenitizing at 900 °C for 180 min. However, the highest Coefficient of friction and resistance of materials to wear are independent of 2 N and 5 N applied loads, while 7 N, 8 N, and 10 N were strongly dependent on the load applied. The outcomes revealed that the Coefficient of friction generally rises as the applied load increases in AGCI and DI. Highest Coefficient of friction 0.8 was observed at 10 N in DI while 0.85 and 0.8 was observed at 10 N and 8 N for AGCI, due to strain-induced retained austenite transformation of the martensite and work hardening.